Distribusi Populasi Sebagai Model Pengembangan Kota Berimbang - Nabal, Alfred Rodriques Januar; Panjaitan, Nofrida; Septianti, Eugenia; Oktapriana, Riesmah; Rachmawaty, Rika; Tenricapa, Siti (Jurnal Pembangunan Wilayah dan Kota, 2020)
Urbanization and global warming are two phenomena that affect urban development. Urbanization increases population concentration and causes complex human activities in urban environments. Meanwhile, the global warming phenomenon causes cities to experience various disasters that threaten the sustainability of human life. The discourse on urban development needs to anticipate these two phenomena. This research aims to determine the form of population distribution in cities as a model for balanced city development through social, economic, and environmental approaches. Â The research method is qualitative, with an instrumental case study approach. The city of Surabaya is an instrument in understanding and formulating an explanation of a balanced city. Literature and document searches are used to collect data and information. The results showed that the social approach of the balanced city has a non-spatial population distribution (functional distribution) pattern which is marked by the functioning of each system in the city and the high level of community participation in creating a balanced city. The economic approach of balanced city has a population distribution pattern that is not determined by the uniformity of population numbers at each city point but emphasizes the aspects of economic benefits that are distributed evenly. The spatial distribution of the population still follows the potential of each region in the city. The environment approach of the balanced city shows the spatial distribution pattern of the population, which refers to the Rencana Tata Ruang Wilayah (RTRW) of a city as a model for balanced city development. A balanced city is a city that through the development of urbanization has grown as a resilient and sustainable city.